Framing Sustainability: Exploring the Impact of Frames on Generation Z’s Perception of Beef Sustainability Messages on Instagram - Kindle G. Catching; Laura Morgan Fischer; Courtney Meyers; Amber McCord (Journal of Applied Communications, 2025)
As sustainability continues to be an emerging conversation in the agricultural industry, the beef sector has come under public scrutiny for its perceived unfavorable environmental impacts such as increased greenhouse gas emissions, water consumption, and animal welfare issues. Organizations within the beef industry are promoting sustainable aspirations to the public and cattle producers have shown priorities to protect the environment on the production side. Even so, environmentally conscious consumers have shown a growing concern for the environmental impact of beef and are beginning to seek out products that more closely align with their values. This study examined three different message frames to determine the impact of framing on Generation Z’s attitude, trust, information processing, and perceptions of posts pertaining to beef sustainability on social media. A survey was distributed to 213 Generation Z college students to collect data regarding participants’ attitude, trust, cognitive processing measures, and demographic information through a Qualtrics survey questionnaire and thought listing procedure. The results revealed no significant differences between the three frames on participant attitudes, trust, or cognitive processing; however, insightful data was obtained through the thought listing procedure included in the survey instrument. The thought listing technique revealed key themes such as information seeking, happiness/hope, and sustainability/environment that were favorable among participants. By promoting messages that highlight the beef industry’s aspirations in consideration of Generation Z’s reported top message content and attributes, communicators can pique viewer interest while also sharing factual information to advance issues that are perceived as unfavorable to the public.
Keywords: Framing; Thought Listing; Heuristic Processing Theory; Sustainability; Social Media